2011
DOI: 10.1007/s13157-011-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influence on Flight Activity and Arrival Patterns of Aerial Colonizers of Temporary Ponds

Abstract: Arrival of aerial insect colonizers was studied (from April to July) using traps (artificial pools) installed adjacent to two temporary ponds in southern Ontario, Canada. The two ponds differed in the length of their hydroperiod: Pond I held water for 98 days, whereas Pond II held water for 34 days. The duration of the study was 15 weeks, during which two phases (wet and dry) were distinguished in each trap according to the presence or absence of water in their respective ponds. Atmospheric, habitat and pond v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
(65 reference statements)
2
7
0
Order By: Relevance
“…On the seasonal timescale, total flight activity of both groups also declined with increasing wind speeds. This is consistent with reported strong declines in flight activity with rising wind speeds or a complete cessation of flight above a certain wind threshold in stoneflies [ 12 ], water beetles and bugs [ 13 , 14 , 18 , 57 ], biting midges [ 22 ], black flies [ 21 ], and swarming chironomids [ 58 ]. In our data, the decline was steeper and wind speed explained a substantial proportion of variability in species composition in terrestrial species.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…On the seasonal timescale, total flight activity of both groups also declined with increasing wind speeds. This is consistent with reported strong declines in flight activity with rising wind speeds or a complete cessation of flight above a certain wind threshold in stoneflies [ 12 ], water beetles and bugs [ 13 , 14 , 18 , 57 ], biting midges [ 22 ], black flies [ 21 ], and swarming chironomids [ 58 ]. In our data, the decline was steeper and wind speed explained a substantial proportion of variability in species composition in terrestrial species.…”
Section: Discussionsupporting
confidence: 88%
“…Their total flight activity declined with relative humidity on both diel and seasonal timescales. Although similar result were found for aquatic beetles and heteropteran bugs [ 18 ], previous studies on dipterans found purely or predominantly positive relationships between relative humidity and flight activity [ 17 , 21 , 22 ]. Aquatic taxa in our study also flew less at higher temperatures at the diel timescale, which contrasted with an increasing trend in flight activity at higher temperatures across the season.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations